2021
DOI: 10.3390/ph14111100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 1-Year Visual and Anatomical Outcomes between Subthreshold Red (670 nm) and Yellow (577 nm) Micro-Pulse Laser Treatment for Diabetic Macular Edema

Abstract: We investigated the efficacy and safety of red (670 nm) subthreshold micropulse laser (SMPL) treatment for diabetic macular edema (DME) and compared the 1-year treatment outcomes of red and yellow (577 nm) SMPL for DME. A medical chart review was performed in 43 consecutive eyes of 35 patients who underwent red or yellow SMPL treatment for DME and were followed up for 12 months. There were 26 and 17 eyes in the yellow and red SMPL groups, respectively. The mean best-corrected visual acuity (BCVA) was maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Overall, a worsening of both BCVA and CMT was not observed in any of the cohorts evaluated [ 29 42 ]. In particular, a significant CMT decrease and BCVA improvement in two thirds were demonstrated [ 29 37 ] and in half of the studies [ 29 , 30 , 33 , 36 , 38 , 40 , 41 ], respectively, whereas a stabilization of these features was described in the remaining cases throughout the entire follow-up [ 31 , 32 , 34 , 35 , 37 42 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Overall, a worsening of both BCVA and CMT was not observed in any of the cohorts evaluated [ 29 42 ]. In particular, a significant CMT decrease and BCVA improvement in two thirds were demonstrated [ 29 37 ] and in half of the studies [ 29 , 30 , 33 , 36 , 38 , 40 , 41 ], respectively, whereas a stabilization of these features was described in the remaining cases throughout the entire follow-up [ 31 , 32 , 34 , 35 , 37 42 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…It allows treatment closer to the fovea. Therefore, there are many research results on diseases such as diabetic macular edema and CSC [19,20] When applied to the skin, the selective photothermolysis system targets the lesion speci cally without causing thermal damage to surrounding tissue, which helps to avoid scarring and dyspigmentation [16].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of MPLT was confirmed in various studies (Table 3) as a statistically significant improvement in or stabilization of best corrected visual acuity (BCVA) and a decrease in CRT [14,16,19,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The first published report on 810 nm micropulsed diode laser was described in 1997 by Friberg et al [55], and it showed clinical effectiveness in the resolution of a DME.…”
Section: Efficacy Of Subthreshold Micropulse Laser and Intravitreal A...mentioning
confidence: 93%
“…A recent study by Kikushima et al [19] compared the 577 nm with the novel 670 nm micropulse treatment. Both the wavelengths seemed to be equally effective, however, the use of the 670 nm laser resulted in less scattering and better penetration.…”
Section: Efficacy Of Subthreshold Micropulse Laser and Intravitreal A...mentioning
confidence: 99%
See 1 more Smart Citation